PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) BERBASIS ANDROID TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Setia Asih, Endah; Yanto, Ari; Dwi Puspitasari, Wina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of Android-based Augmented Reality (AR) learning media on elementary school students’ learning outcomes in the solar system material. This study was motivated by the low learning outcomes of students caused by the use of conventional learning media, which are less effective in visualizing abstract concepts. Solar system material requires concrete understanding because it includes concepts such as planet arrangement, rotation, revolution, and the relationship between celestial bodies. This research employed a quasi-experimental method using the Nonequivalent Control Group Design. The population consisted of all fifth-grade students of SDN Majalengka Wetan VII, totaling 60 students divided into an experimental class and a control class. The sampling technique used was saturated sampling. The research instrument was an essay test administered through pretest and posttest. Data analysis was carried out using descriptive statistics, normality test, homogeneity test, Paired Sample t-Test, Independent Sample t-Test, and N-Gain test with IBM SPSS Statistics 29. The results showed a significant improvement in students’ learning outcomes in the experimental class after using Android-based AR learning media. In addition, there was a significant difference between the experimental and control classes. Therefore, Android-based Augmented Reality (AR) learning media has a positive effect on improving elementary school students’ learning outcomes.